China's urban future and the quest for stability - Clothey, Rebecca A.; Dilworth, Richardson, 1971- (McGill-Queen's studies in urban governance, 2019)
"In recent decades, China has used urbanization as an economic development tool to reconstruct the country's traditional institutions, culture, and society. The downside of these many changes is that they have presented the country's government with a massive challenge: how can it maintain basic stability? China's Urban Future and the Quest for Stability examines the complexities of Chinese cities. Together, the essays in this book explore how the relatively recent onset of urbanization has altered the country, and how that experience is similar to and distinct from developments in other times and places. Each chapter analyzes one facet of China's transformation, focusing on three main themes: urbanization and the rapid growth of Chinese cities; mobility, in both the abstract and the literal sense; and marginalization, evidenced by growing residential segregation in cities and diminishing access to education, health care, and jobs. Underlying these themes is the issue of governance--the systems by which a state attempts to maintain control and achieve its ends, often in ways that differ significantly from what one might expect. An up-to-date, concise, and multidisciplinary collection, China's Urban Future and the Quest for Stability discusses the social, economic, and political forces at work in the urbanization of a modern superpower."--